Logistical Species and Translational Process: A Critique of the Colonial-Imperial Modernity - Solomon, Jon (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2016)
This essay aims to sketch a theory of translation that would be of use in drawing links between three different types of divisions present in all modern societies: the disciplinary divisions within the institutional organization of scientific and humanistic knowledge; the geocultural/geopolitical divisions among global populations; and the economic divisions of labour, both in its external relation to capital and in the internal relations of different forms of labour to subjectivity. We propose that Naoki Sakai’s theory of translation can be fruitfully compared to Gilbert Simondon’s theory of transindividuation, and that the fruits from this comparison can be useful to develop an understanding of the analogical relationships between the three divisions cited above.